(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
They envision a utopian kind of equality that would be codified in Article 14 of the Constitution, which declares that all people are equal before the law regardless of any circumstance. Despite its constrained word count, this article will address the atrocities committed against Dalits, the challenges they have in obtaining justice, and the extent to which the Indian judicial system has adequately addressed these issues. Also covered will be the Prevention of Atrocities Act, which is considered by many to be the first and most important legal measure against inequality.